2014
DOI: 10.1007/s11239-014-1086-1
|View full text |Cite
|
Sign up to set email alerts
|

Solvent/detergent plasma: pharmaceutical characteristics and clinical experience

Abstract: The solvent/detergent treatment is an established virus inactivation technology that has been industrially applied for manufacturing plasma derived medicinal products for almost 30 years. Solvent/detergent plasma is a pharmaceutical product with standardised content of clotting factors, devoid of antibodies implicated in transfusion-related acute lung injury pathogenesis, and with a very high level of decontamination from transfusion-transmissible infectious agents. Many clinical studies have confirmed its saf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 83 publications
(93 reference statements)
0
19
0
1
Order By: Relevance
“…Pathogen inactivation methods used for plasma include solvent/detergent (S/D) treatment and photochemical inactivation techniques [17]. S/D treatment, which is FDA-approved, binds lipid-enveloped viruses and bacteria to inactivate them followed by a filtration process to remove cells and debris, but it has no effect against non-enveloped viruses and prions [48]. Rigorous screening standards require testing donors for non-enveloped viruses twice at a 6-month interval to decrease the risk of transmission.…”
Section: Pathogen Inactivationmentioning
confidence: 99%
See 1 more Smart Citation
“…Pathogen inactivation methods used for plasma include solvent/detergent (S/D) treatment and photochemical inactivation techniques [17]. S/D treatment, which is FDA-approved, binds lipid-enveloped viruses and bacteria to inactivate them followed by a filtration process to remove cells and debris, but it has no effect against non-enveloped viruses and prions [48]. Rigorous screening standards require testing donors for non-enveloped viruses twice at a 6-month interval to decrease the risk of transmission.…”
Section: Pathogen Inactivationmentioning
confidence: 99%
“…Standard S/D treatment causes a decrease in vWF activity (24%), factor V (37%), protein S (44%), and alpha-2 antiplasmin (79%). Similarly, amotosalen + UV light reduces factor VII (23%) and factor VIII (27%) [17,48]. A newer S/D treatment product, Octaplas LG (Octapharma, Lachen, Switzerland), received FDA clearance in 2013 and employs a prion reduction step and a modified S/D process that better preserves factor levels [17].…”
Section: Pathogen Inactivationmentioning
confidence: 99%
“…Studies have shown that there is no significant clinical difference in between S/D plasma and standard plasma. In fact, patients receiving S/D plasma have shown a lower incidence of adverse events such as transfusion‐associated acute lung injury (TRALI) and allergic transfusion reactions . Treatment and donor pooling also provide greater standardization of coagulation factors as compared to single‐donor units of plasma .…”
Section: Resultsmentioning
confidence: 99%
“…S/D-treated plasma has been developed to reduce the risks associated with the use of untreated plasma [62]. The S/D technology virtually eliminates the risk of transmission of enveloped viruses, such as HIV, HBV and HCV.…”
Section: Expert Commentary and Five-year Viewmentioning
confidence: 99%